2019
DOI: 10.3390/ijms21010276
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Alters Functional Properties of CA1 Hippocampal Neurons in Mouse Brain Slices

Abstract: Neuroinflammation is implicated in a host of neurological insults, such as traumatic brain injury (TBI), ischemic stroke, Alzheimer’s disease, Parkinson’s disease, and epilepsy. The immune response to central nervous system (CNS) injury involves sequelae including the release of numerous cytokines and chemokines. Macrophage migration inhibitory factor (MIF), is one such cytokine that is elevated following CNS injury, and is associated with the prognosis of TBI, and ischemic stroke. MIF has been identified in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…MIF is recognized as an important DAMPs molecule following CNS insults. It is immediately elevated after SCI by inducibly expressed in multiple cells including the neurons, oligodendrocytes, microglia, astrocytes and vascular endothelial cells, in association with neuronal apoptosis and demyelination [35,65]. Also, MIF is able to interact with membrane surface receptor CD74 in microglia and astrocytes to activate inflammatory and chemotactic responses [38,66].…”
Section: Discussionmentioning
confidence: 99%
“…MIF is recognized as an important DAMPs molecule following CNS insults. It is immediately elevated after SCI by inducibly expressed in multiple cells including the neurons, oligodendrocytes, microglia, astrocytes and vascular endothelial cells, in association with neuronal apoptosis and demyelination [35,65]. Also, MIF is able to interact with membrane surface receptor CD74 in microglia and astrocytes to activate inflammatory and chemotactic responses [38,66].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, MIF was shown to affect the development and function of various cell types in the CNS, such as astrocytes, microglia and neurons. In addition, MIF is involved in different neurodegenerative diseases, including epilepsy [ 37 , 42 , 43 , 44 , 45 , 75 , 76 ]. For example, Quantitative real-time PCR (qPCR) revealed that MIF transcript gradually increases in brain during development.…”
Section: Discussionmentioning
confidence: 99%
“…Eric et al found that after a single injection of 200 ng exogenous MIF into the mouse hippocampus, the pharmacological kinetics of induced N-methyl-D-aspartic acid receptor (NMDA) responses in the apical dendrites of hippocampal CA1 pyramidal neurons were altered for more than two weeks, which may be responsible for sequelae after CNS injury. 52 In another rat diffuse axonal injury model, cortex MIF levels were considerably elevated 3 hours after injury and were primarily localized in neurons, intracerebroventricular injection of the MIF antagonist ISO-1 reduced neuronal apoptosis and axonal injury. 53 The similar neuronal cell death promotional effects of MIF were found to be involved in other studies, including the traumatic brain injury (TBI) model, which led to more severe neurodegeneration and neurologic deficits.…”
Section: Double Side Effects On Neuronal Cellsmentioning
confidence: 99%